2012
DOI: 10.3109/15569527.2012.727936
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis triggered by tetanus-diphtheria vaccination

Abstract: Psoriasis is a common inflammatory disease with multiple known triggers. We report the case of a patient whose psoriasis was triggered by tetanus and diphtheria immunization (Td vaccine). To the best of our knowledge, this is the first reported case of psoriasis triggered by the Td vaccine. Authors speculate about the involved mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 6 publications
0
26
0
1
Order By: Relevance
“…Although staphylococcal, streptococcal, measles, and varicella vaccines have also been applied previously in the treatment of psoriasis, an early report described two cases of psoriasis induced by BCG vaccination and influenza vaccination under the name of “psoriasis vaccinalis” [ 10 , 20 ]. Subsequently, extremely rare cases of psoriasis, psoriasis-like guttate eruptions, and psoriatic arthropathy have been reported following BCG vaccination and a case of psoriasis was reported, as triggered by the tetanus-diphtheria vaccination [ 11 14 ]. Additionally, a case-control study reported rubella vaccination as a risk factor for psoriatic arthropathy [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although staphylococcal, streptococcal, measles, and varicella vaccines have also been applied previously in the treatment of psoriasis, an early report described two cases of psoriasis induced by BCG vaccination and influenza vaccination under the name of “psoriasis vaccinalis” [ 10 , 20 ]. Subsequently, extremely rare cases of psoriasis, psoriasis-like guttate eruptions, and psoriatic arthropathy have been reported following BCG vaccination and a case of psoriasis was reported, as triggered by the tetanus-diphtheria vaccination [ 11 14 ]. Additionally, a case-control study reported rubella vaccination as a risk factor for psoriatic arthropathy [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was claimed that the vaccination may trigger an exacerbation of psoriatic skin lesions itself; however, these views also concur with the well-known Koebner phenomenon that occurs in psoriasis, that is, the development of new plaques at the locations of skin injury [ 1 ]. Researchers also indicated that the BCG and tetanus-diphtheria vaccines, due to the mycobacterial heat shock proteins in the case of the BCG and diphtheria toxoid in the case of the tetanus-diphtheria vaccines, induce IL-6 production, which, in turn, promotes the development of Th17 cells [ 12 14 ]. Previous studies had also demonstrated a significant increase in IL-6 values after the administration of the influenza vaccination [ 25 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Td vaccine has shown to induce IL-6 production, which stimulates Th17 cells, having a key role in psoriasis pathogenesis [37,38]. It was suggested that this mechanism was the triggering cause in this case [37].…”
Section: Tetanus-diphtheria (Td) Vaccinationmentioning
confidence: 99%
“…A case of 50-year-old psoriasis patient in remission was described as guttate psoriasis 1 week after the Td vaccination [37]. Td vaccine has shown to induce IL-6 production, which stimulates Th17 cells, having a key role in psoriasis pathogenesis [37,38].…”
Section: Tetanus-diphtheria (Td) Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation